Status and Future of the EDEN ISS Mobile Test Facility - Vrakking, Vincent; Zabel, Paul; Zeidler, Conrad; Dorn, Markus; Schubert, Daniel (2020)
Within the EDEN ISS project an international consortium designed and built a (semi-)closed loop greenhouse, called the Mobile Test Facility, to investigate and validate techniques for plant cultivation in future bioregenerative life support systems. At the end of 2017 the Mobile Test Facility, consisting of two modified 20 foot shipping containers, was transported to the German Neumayer Station III in the Antarctic for testing in a space-analogue environment. Following arrival in the Antarctic in January 2018, and initial system checkout activities, the Mobile Test Facility began its first operational phase in February 2018. Although the EDEN ISS project foresaw only one year of operations and the project has officially concluded, the Mobile Test Facility remains in the Antarctic, operating at least until the end of 2020 and possibly beyond. This paper describes initial results and lessons learned from the 2018 and 2019 operations of the Mobile Test Facility, and presents an overview of the intended activities for 2020 and beyond.